Using Pollution Index to determine water quality in Banda Aceh waters, Indonesia - ondara, Koko; Wisha, Ulung Jantama; Agustina, Sri; Atmadipoera, Agus saleh; Purnawan, Syahrul (Jurnal Rekayasa Kimia & Lingkungan, 2022)
The northern waters of Banda Aceh are connected with the Indian Ocean, the Andaman Sea, and the Malacca Strait, thus making the study of water quality parameters in this region is important for enviromental management. In this study, water quality parameters are measured spatially and then continued with assessing the pollution index. The results can be helpful for development planning and coastal pollution mitigation in Banda Aceh. The data was collected from 21 seawater samples from 11 stations representing the water of Banda Aceh on 10-11 September 2019. VanDorn bottles were used to store the seawater samples for laboratory analysis. Several parameters such as temperature, salinity, and pH were measured in situ, while other parameters were tested in the laboratory. Most heavy metal parameters showed values below the minimal and maximal value limit detection of the instrument, indicating a small potential for heavy metal contamination. However, the pollution index (PI) indicates the potential for water pollution dominated by nitrate and phosphate with a value that exceeds the water quality standard. The indications are shown from the high aquaculture and anthropogenic activities around the coast of Banda Aceh.